Blockade of Mas Receptor or Mas-Related G-Protein Coupled Receptor Type D Reduces Portal Pressure in Cirrhotic but Not in Non-cirrhotic Portal Hypertensive Rats - Gunarathne, Lakmie S.; Angus, Peter W.; Herath, Chandana B. (Frontiers in Physiology, 2019)
Portal hypertension (PHT) resulting from splanchnic vasodilatation is a major cause of morbidity and mortality in patients with cirrhosis. The renin-angiotensin system (RAS) plays an important role in splanchnic vasodilatation in cirrhosis. This study investigated whether acute blockade of the vasodilatory receptors of the alternate RAS, Mas (MasR), Mas-related G-protein coupled receptor type D (MrgD) and angiotensin II type-2 receptor (AT2R), improves PHT in cirrhotic and non-cirrhotic portal hypertensive rats and counteracts systemic hypotension associated with angiotensin II type 1 receptor (AT1R) blockade. Cirrhotic bile duct ligated (BDL) or carbon tetrachloride (CCl4) injected and non-cirrhotic partial portal vein ligated (PPVL) rats were used for measurement of portal pressure (PP) and mean arterial pressure before and after an intravenous bolus injection of the MasR, MrgD and AT2R blockers, A779, D-Pro7-Ang-(1-7) (D-Pro) and PD123319, respectively. Separate groups of rats received a combined treatment with A779 or D-Pro given 20 minutes after AT1R blocker losartan. Mesenteric expression of MasR, MrgD and AT2R and circulating levels of peptide blockers were also measured. Treatment with A779 and D-Pro significantly reduced PP in cirrhotic rat models. Despite rapid degradation of A779 and D-Pro in the rat circulation, the PP lowering effect of the blockers lasted for up to 25 min. We also found that PD123319 reduced PP in CCl4 rats, possibly by blocking the MasR and/or MrgD since AT2R expression in cirrhotic mesenteric vessels was undetectable whereas the expression of MasR and MrgD were markedly elevated. Whilst losartan resulted in a marked reduction in PP, its profound systemic hypotensive effect was not counteracted by the combination therapy with A779 or D-Pro. In marked contrast, none of the receptor blockers had any effect on PP in non-cirrhotic PPVL rats whose mesenteric expression of MasR and MrgD was unchanged. We conclude that in addition to MasR, MrgD, a newly discovered receptor for Angiotensin-(1-7), plays a key role in splanchnic vasodilatation in cirrhosis. This implies that both MasR and MrgD are potential therapeutic targets to treat PHT in cirrhotic patients. We also conclude that the alternate RAS may not contribute to the development of splanchnic vasodilatation in non-cirrhotic PHT.